2019 27th European Signal Processing Conference (EUSIPCO) 2019
DOI: 10.23919/eusipco.2019.8902531
|View full text |Cite
|
Sign up to set email alerts
|

On the Physical Layer Security of IoT Devices over Satellite

Abstract: The security in satellite communications is a key issue due to the large footprint of the beams. This it is specially critical in IoT devices that transmit data directly to satellite. Take into account that IoT devices are characterized by transmitting packets of short length. Consequently, it means that it is not feasible to augment the security level of the IoT packets via complex cryptographic algorithms. Otherwise, their packed length may be increased in a non-negligible way which could augment their colli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…and β = 1/σ 2 Y of the Gamma-Gamma distribution in (20) are directly related to the atmospheric conditions, and for the untracked beam case are given:…”
Section: Atmospheric Turbulence: Beam Wander Beam Spreading and Beam Scintillationmentioning
confidence: 99%
See 1 more Smart Citation
“…and β = 1/σ 2 Y of the Gamma-Gamma distribution in (20) are directly related to the atmospheric conditions, and for the untracked beam case are given:…”
Section: Atmospheric Turbulence: Beam Wander Beam Spreading and Beam Scintillationmentioning
confidence: 99%
“…From the satellite point of view, the possibility of reducing the transmission time without augmenting the transmission bandwidth fits very well for overcoming the drawbacks of the optical channel, which heavily depend on atmospheric conditions such as clouds [6]. By doing so, the link layer may adjust the transmission time of the frames without reducing the number of symbols to transmit according to weather forecasts [20].…”
Section: Introductionmentioning
confidence: 99%
“…By doing so, the minimum Euclidean distance between received constellation points did not change, enabling a higher data rate without augmenting the communication bandwidth. With the implementation of timepacking, the use of high-order modulations could be avoided; therefore, this signaling is specially appealing for satellite systems with optical feeder link, as the Peak-to-Average Power Ratio (PAPR) of the transmit signal does not grow notably, and thus the power of the non-linear distortion and the signaldependent noise that are added can be kept low [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…More precisely, it was shown that in presence of a binary sequence of Sincpulses, a 25%-data-rate-increase was feasible by shrinking the time between adjacent Sinc-pulses to about 80.2% of the Nyquist symbol time. Unfortunately, in order to capitalize this gain, the complexity of the detector must grow notably when the roll-off factor of the Sinc-pulses decreases, the overlapping factor between adjacent Sinc-pulses grows, and/or the order of the modulation scheme augments [5], [6]. For this reason, it is necessary to study the performance of low-complexity linear detectors, as the performance of Maximum-Likelihood Sequence Estimation (MLSE) impairs notably when the number of trellis states in the Viterbi algorithm is limited [7].…”
Section: Introductionmentioning
confidence: 99%